Audubon North American birdfeeder guide - Burton, Robert, 1941- (DK, 2010)
An illustrated handbook of bird identification provides tips on the art of birdwatching, closeup illustrations, locater maps, birding etiquette, essential equipment, and tips on the best ways to attract, feed, and observe various bird species in one's own backyard.